Crystals of Na(+)/K(+)-ATPase with bound cisplatin - Huliciak, Miroslav; Reinhard, Linda; Laursen, Mette; Fedosova, Natalya; Nissen, Poul; Kubala, Martin (Biochemical pharmacology, 2014)
Cisplatin is the most widely used chemotherapeutics for cancer treatment, however, its administration is connected to inevitable adverse effects. Previous studies suggested that cisplatin is able to inhibit Na(+)/K(+)-ATPase (NKA), the enzyme responsible for maintaining electrochemical potential and sodium gradient across the plasma membrane. Here we report a crystallographic analysis of cisplatin bound to NKA in the ouabain bound E2P form. Despite a moderate resolution (7.4 Å and 7.9 Å), the anomalous scattering from platinum and a model representation from a recently published structure enabled localization of seven cisplatin binding sites by anomalous difference Fourier maps. Comparison with NKA structures in the E1P conformation suggested two possible inhibitory mechanisms for cisplatin. Binding to Met151 can block the N-terminal pathway for transported cations, while binding to Met171 can hinder the interaction of cytoplasmic domains during the catalytic cycle.
Keywords: Sodium pump; Models, Molecular; cisplatina; Cisplatin; ouabain; Protein Conformation; krystalografie rentgenová; Crystallography, X-Ray; molekulární modely; sodíko-draslíková ATPasa; Ouabain; Adverse effects; methionin; Methionine; Sodium-Potassium-Exchanging ATPase; Na(+)/K(+)-ATPase; X-ray crystallography; terciární struktura proteinů; Binding sites; Protein Structure, Tertiary; konformace proteinů